Academic Staff’s Motivation for Online Teaching in Nigerian Universities: Empirical Evidence from the University of Ibadan (2022)
This study investigated the academic staff’s motivation for online teaching in Nigerian universities using a mixed-methods case study research design. The main instrument used for this study was a questionnaire named ‘Academic Staff’s Motivation for Online Teaching Survey (SMOTS)', which was complemented by in-depth interviews. A total of 195 academic staff across various academic faculties and units in the University of Ibadan participated in the study. Data analysis was done using frequency count, simple percentages, mean and standard deviation, while the in-depth interviews were thematically analysed. The result of the study revealed that the majority of the academic staff have not taught using online platforms before and their frequency of online teaching consideration is occasional. Additionally, they have a high perception of online teaching in terms of helping to learn new technology and encouraging intellectual challenges. The academic staff indicated that individual training opportunities, personal decisions and group training opportunities are among the major resources that can motivate them for online teaching. Likewise, the introduction to new technology for teaching, institutional expectation, and students’ enrolment are the major external motivating factors for online teaching.